Teachers’ Reading Strategies in Developing Elementary ESL Learners’ Oral Reading Fluency (ORF) - Ocampo, Darrel; Abergos, Julie Ann; Garfin, Jane; Cardinal, Willy (Universitas Terbuka, 2025)
This study aimed to determine the reading strategies utilized by the teachers in developing oral reading fluency of learners in the First District of Camarines Sur, Bicol, Philippines. Descriptive method was used to describe demographic profile of the respondents, the extent of teaching reading strategies, and the perceived effect of the teaching strategies utilized by the teachers in developing oral reading fluency. The correlational method was utilized to ascertain the relationship between the demographic profile and the extent of teaching reading strategies. 93 English Elementary teachers served as the respondents. Results disclosed that solitary reading, buddy reading, and group reading have a Very Large Extent in developing oral reading fluency. Accuracy, automaticity, and prosody proved to be highly effective in developing oral reading fluency among learners. Moreover, the extent of utilizing solitary reading, buddy reading, and group reading is not significantly correlated in terms of academic rank, years of teaching, and highest educational attainment of the teachers. The lack of significant correlation implies that the implementation of solitary, buddy, and group reading practices is likely more influenced by contextual and pedagogical considerations than by the demographic or educational attributes of the teachers. To further investigate, longitudinal studies or qualitative research might provide deeper insights into how teachers select and implement reading practices in response to evolving educational needs and environments. It may also be beneficial to explore how these reading practices affect student outcomes, as this could offer critical feedback for instructional improvement.